TALENT ACQUISITION DAN TALENT ON BOARDING PADA INDUSTRI PARIWISATA DI BINTAN - Alden Nelson,; Angeline, Angeline; Angela Adriyanti Yang,; Dennis Yang,; Leonard Suryadi Yusuftan,; Whitney Ong, (Jurnal Cakrawala Ilmiah, 2022)
This research was made to know and analyze the Talent Management Model, Talent Management Study to Talent Management Mapping from companies in the tourism sector, spesifically resort in Bintan island. The method used in this research is a method of searching data from the internet and available materials. For data analysis, the author will use the components mentioned to analyze how the companies of tourism sector in Bintan island manages its talent from planning, attracting, developing, and retaining to transitioning. Then the author gets the companies using a combination of 2 strategies for the talent management strategy, namely by hiring only top employees and hiring promising specialists and developing them. And finally the use of 9 boxes of talent mapping will be used by the author to analyze talent from the tourism sector in Bintan island. The author suggests that companies need to carry out an evaluation process for each of their employees and also inform HR to train and monitor the performance of managers.